2015
DOI: 10.5194/acp-15-5803-2015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling study of PM<sub>2.5</sub> pollutant transport across cities in China's Jing–Jin–Ji region during a severe haze episode in December 2013

Abstract: Abstract.To study the influence of particulate matter (PM) transported from surrounding regions on the high PM 2.5 pollution levels in Beijing, the GRAPES-CUACE model was used to simulate a serious haze episode that occurred on 6-7 December 2013. The results demonstrate the model's suitability for describing haze episodes throughout China, especially in the Beijing-Tianjin-Hebei (Jing-Jin-Ji) region. A very close positive correlation was found between the southerly wind speed over the plain to the south of Bei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 46 publications
3
63
0
Order By: Relevance
“…The large amount of PM 2.5 inflows can only be efficiently blown out to the northeast direction (Chengde, Langfang (N) and Tianjin (N)). These results are consistent with Jiang et al (2015), who also found a strong southerly input at a high level during a haze episode in winter.…”
Section: The Daily Characteristics Of Pm 25 Transport In Beijingsupporting
confidence: 82%
“…The large amount of PM 2.5 inflows can only be efficiently blown out to the northeast direction (Chengde, Langfang (N) and Tianjin (N)). These results are consistent with Jiang et al (2015), who also found a strong southerly input at a high level during a haze episode in winter.…”
Section: The Daily Characteristics Of Pm 25 Transport In Beijingsupporting
confidence: 82%
“…In an urban and industrialized region, anthropogenic emissions from traffic, domestic heating, factories, power plants and biomass burning significantly elevate the concentrations of these (and other) trace gases (TGs) in the boundary layer (Environmental Protection Agency, 1998;Seinfeld and Pandis, 1998). There is strong evidence that aerosol particles formed through photochemistry of NO x , SO 2 and VOCs significantly contribute to haze pollution events occurring frequently around megacities and urban agglomerations in China, like the Jing-Jin-Ji region and the Yangtze River delta region Huang et al, 2014;Jiang et al, 2015;Fu et al, 2014). The aerosols also impact the local radiative forcing through direct (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The overestimation of PM 2.5 in this study might be attributed to the uncertainties of these three factors in the model. Prior studies (Zhou et al, 2012;Wang et al, 2015a, b;Jiang et al, 2015) have demonstrated the stable simulation performance of the GRAPES-CUACE modeling system in reproducing air pollution levels and variation trends over northeast China. Above all, the following analysis mainly focuses on the variations and the contributing proportions of emission sources over different regions.…”
Section: Model Setup Data and Validationmentioning
confidence: 99%
“…The GRAPES-CUACE is an online coupled atmospheric chemistry modeling system (Wang et al, 2009;Zhou et al, 2012;Jiang et al, 2015) developed by the China Meteorological Administration (CMA). GRAPES-Meso is a regional meteorological model (Xue et al, 2008) within GRAPES-CUACE, and CUACE is an atmospheric chemistry modeling system independent of meteorological and climate models.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation